Teacher Mate: A Support Tool for Teaching Code Quality - de Araújo, Darlan Murilo Nakamura [UNESP]; Eler, Danilo Medeiros [UNESP]; Garcia, Rogério Eduardo [UNESP] (Springer Nature, 2020)
In introductory courses of technology, students with difficulty in programming subjects have led to high dropout rates due to difficulties to understand algorithms, programming language, and paradigm concepts. Furthermore, teachers encounter challenges to support students individually, when adequate feedback is essential to the learning process. This paper presents the Teacher Mate tool to support source code analysis to identify the lack of good programming practices and to evidence students’ difficulties. We performed a case study focusing on identifying the difficulties among six classes of a object-oriented programming course. Our findings show that difficulties are similar in all classes and the students applied some concepts accurately (such as the encapsulation) and fewer violations remain on the source code. Moreover, we show an intervention and its result: based on analysis, the teacher modifies the approach, leading to positive results to support learning both object-oriented concepts and source code quality.
Keywords: Code quality; Learning tool; Object-oriented concepts; Source code analysis; Technology for instruction